Non-Destructive Evaluation of Coating Thickness Using Water Immersion Ultrasonic Testing - Jiannan Zhang (MDPI AG, 2021)
The coating is applied to prevent corrosion on the surface of ships or marine structures, and the thickness of the coating affects its anti-corrosion effect. As a result, non-destructive testing (NDT) is required to measure coating thickness, and ultrasonic NDT is a convenient and quick way to measure the thickness of underwater coatings. However, the offshore coating’s energy attenuation and absorption rates are high, the ultrasonic pulse echo test is difficult, and the testing environment is harsh. Because of the coating’s high attenuation, the distance of the optimal water delay line designed based on the reflection coefficient of the vertically incident wave is used. To accurately measure the thickness of the coating material, TOF of the reflected echo on the time-domain waveform was evaluated. The experimental results show that, when compared to caliper measurements, the coating thickness measured by the proposed method has a lower error and can be used for accurate measurement. The use of ultrasonic water immersion measurement is almost limitless in terms of size, location, and material of the object to be measured, and it is expected to be used to measure the thickness of the surface coating of ships or marine structures in the water.